Antibiotic resistance in wastewater treatment plants: Tackling the black box - Manaia, CM (2018)
Wastewater is among the most important reservoirs of antibiotic resistance in urban environments. The abundance of carbon sources and other nutrients, a variety of possible electron acceptors such as oxygen or nitrate, the presence of particles onto which bacteria can adsorb, or a fairly stable pH and temperature are examples of conditions favouring the remarkable diversity of microorganisms in this peculiar habitat. The wastewater microbiome brings together bacteria of environmental, human and animal origins, many harbouring antibiotic resistance genes (ARGs). Although numerous factors contribute, mostly in a complex interplay, for shaping this microbiome, the effect of specific potential selective pressures such as antimicrobial residues or metals, is supposedly determinant to dictate the fate of antibiotic resistant bacteria (ARB) and ARGs during wastewater treatment. This paper aims to enrich the discussion on the ecology of ARB& ARGs in urban wastewater treatment plants (UWTPs), intending to serve as a guide for wastewater engineers or other professionals, who may be interested in studying or optimizing the wastewater treatment for the removal of ARB& ARGs. Fitting this aim, the paper overviews and discusses: i) aspects of the complexity of the wastewater system and/ or treatment that may affect the fate of ARB& ARGs; ii) methods that can be used to explore the resistome, meaning the whole ARB & ARGs, in wastewater habitats; and iii) some frequently asked questions for which are proposed addressing modes. The paper aims at contributing to explore how ARB& ARGs behave in UWTPs having in mind that each plant is a unique system that will probably need a specific procedure to maximize ARB& ARGs removal.